Pembelajaran Bahasa Arab Interaktif melalui Media E-Learning Madrasah di MTsN 1 Kota Malang - Siti Nurul Fitriani; Syarifah Syarifah; Ali Susanto (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2020)
This paper aims to describe the use of Madrasah E-Learning as a modern learning Arabic with an easy and fun application and includes four maharohs. To meet these objectives, researchers used descriptive qualitative research methods. The results are (1) Madrasah E-Learning is a modern Arabic learning that is used online in Distance Learning (2) Madrasah E-Learning provides several main Arabic learning menus such as Class Timeline, Video Conference, Minimum Completeness Criteria, Learning Plans, Teaching Materials, Associated Student Data, Class Attendance, Teacher`s Journal, Computer Based Test (CBT), Knowledge Assessment (KI3), Skill Assessment (KI4), Final Semester Assessment, Report Card Recapitulation, Student Activity Monitoring. The research method that researchers use in this research is qualitative method research.